Fermented beverages in prehispanic Chile: a comprehensive review of their phytochemistry, traditional medicinal uses, bioactivity, and social aspects - Mitsi, Christina; Echeverría, Javier (Frontiers in Pharmacology, 2024)
Background: Archaeological, ethnohistorical, and ethnographic evidence supports the ubiquitous use of fermented beverages in prehispanic Chile. Made from a variety of plant raw materials, these beverages have been of special importance regarding many nutritional, medicinal, social, ritual, and religious aspects.The present review aims to provide a comprehensive review of the interdisciplinary information on traditional Chilean fermented beverages, as well as on the starting materials used for their elaboration.Materials and Methods: Anthropological and ethnopharmacological data were collected through literature searches based on archaeological evidence, books from chroniclers and explorers, as well as modern ethnographic testimonies. Literature data on the chemistry and bioactivity of the prehispanic fermented beverages and the raw materials used were mainly retrieved from digital databases such as SciFinder®, PubMed®, and Google Scholar®.Results and Discussion: Thirty seven plant raw materials have been used for the elaboration of traditional fermented beverages in prehispanic Chile. Phytochemical and bioactivity data regarding these beverages are rather limited, but a wide spectrum of chemical compounds, health-promoting and disease-preventative effects is reported for the starting materials.Conclusions: Despite the lack of scientific evidence on traditional prehispanic fermented beverages of Chile, the plant raw material exhibit promising phytochemical profiles and potential health-promoting and disease-preventative benefits. This review underscores the importance of integrating ethnopharmacological perspectives into modern research endeavors.